Asante kete lead and support drumming in Yaw Daniel Okyere's palace ensemble at Mampong, Ghana. - Montes, Teresa A. (2011.)
This thesis focuses on Kete, a drum and dance court tradition of the Asante people of Ghana. Kete as a dynamic, complex musical phenomenon that plays a significant role in Asante and culture. Its performances are a major component in music-making for social events such as funerals and durbars. A durbar is a ceremonial formal gathering called by a governmental authority.
Thesis (B.M.)--University of the Philippines, Diliman.